Functional Impact of Tinnitus in Patients with Hearing Loss - Mantello,Erika Barioni (2020)
Abstract Introduction Tinnitus, which is considered the third worst symptom for humans, is a common complaint among people living with hearing loss and may negatively affect the quality of life of those who have it. Objective To analyze the perception of the handicap in patients with tinnitus and hearing loss as well as the possible associations between the variables hearing loss, loudness, onset, frequency and annoyance by tinnitus, and the correlation between the visual analogue scale (VAS) and the Tinnitus Handicap Inventory (THI). Methods A total of 30 patients with complaints of tinnitus and the presence of sensorineural hearing impairment were selected for this cross-sectional, observational, and descriptive study. The loudness of the tinnitus was measured by a VAS and classified as mild,moderate, or severe. The THI was classified as slight, mild, moderate, severe, and catastrophic. Data were submitted to statistical analysis using the Fisher exact test and Spearman correlation coefficient. Results Eleven male (36.7%) and 19 female (63.3%) subjects with a mean age of 56.5 years old were evaluated. There was no significant association between loudness, annoyance, time and frequency of tinnitus, nor between hearing loss and tinnitus. There was a significant association between the variables hearing loss and loudness, and a weak correlation between VAS and THI. Conclusion Tinnitus has a practical impact in the lives of patients with hearing loss in terms of catastrophic, functional, and emotional aspects, regardless of loudness, frequency, or time of onset. Hearing loss was a factor that had an impact on the loudness of tinnitus. There was no statistically significant correlation between VAS and THI.